2011
DOI: 10.1097/brs.0b013e3181ffde92
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Upright Posture Induces Calcified Hypertrophy in the Cartilage End Plate in Rat Lumbar Spine

Abstract: Prolonged upright posture induces cartilage end plate calcification and hypertrophy in rat lumbar spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…We have previously found that excess activation of TGFβ causes sclerosis and angiogenesis of subchondral bone in the knee joint, which alters loading distribution on articular cartilage and is key in the pathogenesis of osteoarthritis (OA) 7 8 . Upregulation of TGFβ has been observed in calcified hypertrophic EPs of degenerative IVD 9 . Whether TGFβ is involved in EP sclerotic changes is unknown.…”
mentioning
confidence: 99%
“…We have previously found that excess activation of TGFβ causes sclerosis and angiogenesis of subchondral bone in the knee joint, which alters loading distribution on articular cartilage and is key in the pathogenesis of osteoarthritis (OA) 7 8 . Upregulation of TGFβ has been observed in calcified hypertrophic EPs of degenerative IVD 9 . Whether TGFβ is involved in EP sclerotic changes is unknown.…”
mentioning
confidence: 99%
“…E nd-plate calcification correlates with the process of vertebral disc degeneration, which can cause or promote the process of intervertebral disc disease 7,21 . Mechanical strain is one of the causes of calcification 13 . In this study, chondrocytes stained positively with AR-S at pH 4.2, showing that mechanical strain can induce calcification in endplate chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell growth, differentiation and function can be influenced by appropriate mechanical strain stimulation; excessive mechanical stimulation can damage cell structure. Previous studies have shown that mechanical stress is associated with calcification of the lumbar spine cartilage endplate 13 , which could affect the metabolism and functioning of the disc, then accelerate the process of intervertebral disc degeneration 14 . For testing purposes, 1000 m is probably an appropriate degree of physiological strain, no more than 4000 m strain occurs during vigorous physiological activity in humans 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A series of changes in the disc have been observed with aging, such as endplate calcification and disc degeneration. 4 , 5 Abnormal endplate calcification is observed in a disc degeneration model of mechanical instability in the cervical or lumbar spine. We therefore speculate that changes in endplate calcification are related to mechanical stress.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 is also able to induce extracellular pyrophosphate (ePPi) up-regulation via TGF-β1-induced Ank gene expression. 4 , 7 …”
Section: Introductionmentioning
confidence: 99%